Duplication of single stranded DNA catalyzed by calf thymus DNA polymerase alpha. - Wang, E (1976)
Purified calf thymus DNA polymerase alpha is inactive with native DNA as template and shows little activity with denatured DNA. DNA synthesis with denatured DNA as template is greatly stimulated by the addition of a nuclease which initially copurifies with DNA polymerase but is separated from the polymerase on DEAE-cellulose chromatography. A limit digest of nuclease treated native DNA which is then denatured is replicated 80-95%; extensive replication is also obtained with native DNA partially degraded by pancreatic DNase and then denatured. The product of the reaction with calf thymus nuclease-treated DNA as template is double-stranded DNA with a hairpin (looped back) structure.